A MODERN JUDICIAL SYSTEM IN INDONESIA: LEGAL BREAKTHROUGH OF E-COURT AND E-LEGAL PROCEEDING - Putra, Dedi (Jurnal Hukum dan Peradilan, 2020)
The implementation of court in Indonesia has not fulfilled as expected because any parties involving in court has a lack of capacity, consistency, and integrity to provide legal service seriously. Some people assume that court services are not still optimal. To settle the problems, the Supreme Court just has officially issued Regulation No. 1 of 2019 regarding the Administration of Cases and Legal Proceedings in Courts via Electronic Means on 8 August 2019. This regulation is believed as an appropriate solution to face those problems. To elaborate more, this study illustrates a judicial reform in Indonesia, e-court, and access to justice, the conception of e-court including the performance of e-court and its drawbacks and challenges in the digital era. The research method uses normative research by approaching legal review and literature study. The technique of primary data collection applies Supreme Court regulation while means of secondary data are collected from concept or theory as set out under bibliography. Judicial reform in Indonesia is indicated by issuing new regulation regarding e-Court and e-Litigation, the implementation e-Court itself has been attributed to 32 courts consisting of general religious, and state administrative courts. Through e-Court, access to justice more transparent and accessible. Besides, justice seekers have no worries regarding distance issues as of e-Court may allow them to fight in court without face to face. Parties have no doubt relating to the acceleration of court to settle any dispute in Indonesia.